Reassessment of oxidative stress in idiopathic sudden hearing loss and preliminary exploration of the effect of physiological concentration of melatonin on prognosis - Song, Jianxiong; Ouyang, Fang; Xiong, Yuanping; Luo, Qing; Jiang, Hongqun; Fan, Li; Zhang, Zhiyuan (Frontiers in Neurology, 2023)
Background and purpose The pathogenesis of idiopathic sudden sensorineural hearing loss (ISSNHL) is still unclear, and there is no targeted treatment. This research aimed to verify the role of oxidative stress in ISSNHL and explore whether melatonin has a protective effect on hearing. Materials and methods A total of 43 patients with ISSNHL and 15 healthy controls were recruited to detect the level of melatonin, reactive oxygen species (ROS), and total antioxidant capacity (TAC) in the blood and compared before and after treatment. Multivariate logistic regression models were performed to assess the factors relevant to the occurrence and improvement of ISSNHL. Results The patients with ISSNHL showed significantly higher ROS levels than controls (4.42 ± 4.40 vs. 2.30 ± 0.59; p = 0.031). The levels of basal melatonin were higher (1400.83 ± 784.89 vs. 1095.97 ± 689.08; p = 0.046) and ROS levels were lower (3.05 ± 1.81 vs. 5.62 ± 5.56; p = 0.042) in the effective group as compared with the ineffective group. Logistic regression analysis showed that melatonin (OR = 0.999, 95% CI 0.997–1.000, p = 0.049), ROS (OR = 1.154, 95% CI 1.025–2.236, p = 0.037), and vertigo (OR = 3.011, 95% CI 1.339–26.983, p = 0.019) were independent factors associated with hearing improvement. Besides, the level of melatonin (OR = 0.999, 95% CI 0.998–1.000, p = 0.023) and ROS (OR = 3.248, 95% CI 1.109–9.516, p = 0.032) were associated with the occurrence of ISSNHL. Conclusion Our findings may suggest oxidative stress involvement in ISSNHL etiopathogenesis. The level of melatonin and ROS, and vertigo appear to be predictive of the effectiveness of hearing improvement following ISSNHL treatment.